Characterization of fully-evaporated perovskite solar cells and photodetectors under high-intensity pulsed proton irradiation - Hryhorii P. Parkhomenko; Andrii I. Mostovyi; Marat Kaikanov; Jessica Strey; M. Turcu; Marvin Diederich; Sascha J. Wolter; Verena Steckenreiter; Joachim Vollbrecht; В. В. Брус (Springer Science and Business Media LLC, 2024)
This study investigates the impact of proton irradiation on perovskite devices fabricated fully through vacuum deposition. Exposure to irradiation induces changes in both electrical and optical properties. The analysis reveals that the main factors influencing the observed performance changes in solar cells are a significant reduction in shunt resistance and a minor increase in series resistance, with minimal alterations in recombination dynamics. Remarkably, the devices maintain promising photodetector characteristics both before and after proton irradiation, particularly in a self-powered mode without a reverse bias. These findings provide valuable insights into the resilience of vacuum-deposited perovskite devices against ionizing radiation, highlighting their potential for applications in radiation-prone environments, such as the nuclear industry or space exploration.
Keywords: Irradiation; Perovskite (structure); Photodetector; Materials science; Optoelectronics; Radiation tolerance; Ionizing radiation; Proton; Radiation resistance; Radiation; Optics; Chemistry; Physics; Radiation therapy; Quantum mechanics; Nuclear physics; Crystallography; Medicine; Internal medicine; type of access: open access